Metal-free approach for the ʟ-proline mediated synthesis of nitrones from nitrosobenzene. Issue 31 (2nd August 2018) - Choi, Minho; Viji, Mayavan; Kim, Donghwan; Lee, Young Hee; Sim, Jaeuk; Kwak, Young-Shin; Lee, Kiho; Lee, Heesoon; Jung, Jae-Kyung
Abstract: An efficient, and metal-free approach for the ʟ-proline mediated synthesis of nitrones from nitrosobenzene and benzaldehydes has been established. The reaction undergoes very efficiently at room temperature in methanol as a solvent. The reaction is assumed to involve that the initial formation of azomethine ylide and [2 + 3] cycloaddition of nitrosobenzene, followed by the subsequent retro [2 + 3] cycloaddition could offer the desired nitrone. Graphical abstract: Image 1 Highlights: This is simple reaction and completed in shorter reaction time. It is a metal-free reaction, utilizing environmentally benign ʟ-proline as reagent. Wide substrates scope with various aromatic and hetero aromatic aldehydes. Proposed mechanism has also been given to understand reaction pathway.